Synthesis, characterization, in vitro antioxidant and antimicrobial activities of diorganotin(IV) complexes derived from hydrazide Schiff base ligands. (2nd December 2021) - Devi, Jai; Pachwania, Sushila
Abstract: We have synthesized new diorganotin(IV) complexes of the type R2 SnL (where R; methyl, ethyl, butyl and phenyl) of Schiff base ligands N'-(5-chloro-2-hydroxybenzylidene)thiophene-2-carbohydrazide (H2 L 1 ), N'-(4-(diethylamino)-2-hydroxybenzylidene)thiophene-2-carbohydrazide (H2 L 2 ), N'-(3, 5-dibromo-2-hydroxybenzylidene)thiophene-2-carbohydrazide (H2 L 3 ) and N'-(2-hydroxy-5-methoxy-3-nitrobenzylidene)thiophene-2-carbohydrazide (H2 L 4 ). Spectroscopic methods (FT-IR, UV–vis, 1 H, 13 C and 119 Sn NMR), elemental analysis, mass spectrometry, melting point and molar conductance measurements were used to elucidate the structures of compounds (1-20). The spectroscopic data indicated that the Schiff bases are tridentate (NOO) in nature and coordinated to the tin metal through enolic oxygen, azomethine nitrogen and aromatic hydroxyl oxygen donor atoms to display pentacoordinated geometry around the central tin metal. To examine the biological profile, the synthesized compounds were tested for in vitro antimicrobial activity against different bacterial and fungal strains by using serial dilution method which revealed that compounds Bu2 SnL 3 (15 ) and Ph2 SnL3 (16 ) were most active antimicrobial agent. The compounds were further tested for antioxidant activity by using DPPH (1, 1-diphenyl-2-picrylhydrazyl) assay. Complex Ph2 SnL 3 (16 ) exhibited highest antioxidant potential with lowest IC50 value (2.95 μM) among all the tested compounds. Graphical Abstract: UF0001